Kualitas dan Efektivitas Sistem Informasi Berbasis Komputer - Baridwan, Zaki; Hanum, Latifah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
Information system refers to a highly valuable resource for an organization because the organization really needs this kind of resources to ascertain the perfection, effectiveness and efficiency. To avoid from rejection to the developed information system needs to improve information system quality because it affects the user satisfaction rate for the development system. Research aims at observing whether three dimensions of quality, such as information quality, system quality, and service quality affect the effectiveness of information system. This effectiveness relies on the user satisfaction rate. Pursuing this research objective, the used analysis to examine Hypothesis 1 (H I), Hypothesis 2 (H2), and Hypothesis 3 (H3) constitutes multiple-regression statistic test. Research sample includes the employee or the user o f information system in 9 types o f company or institution located at East Java, with total reaching 126 participants. Results of classic assumption fesf indicate that multicolinearity, autocorrelation, and heteroscedasticity don't develop in the regression model. F test shows that Information Quality, System Quality, and Service Quality simultaneously affect the Computer based Information System Effectiveness. Results of research determine that system quality and service quality have significant effect on system effectiveness, while information quality doesn’t significantly affect system effectiveness. This becomes evident due to lack of employee's knowledge about the system and shorter work incumbent among the employee. Key words: Information Quality. System Quality, Service Quality, System Effectiveness, Computer-based Information System